2002
DOI: 10.1073/pnas.182314699
|View full text |Cite
|
Sign up to set email alerts
|

A duplicated copy of DMRT1 in the sex-determining region of the Y chromosome of the medaka, Oryzias latipes

Abstract: The genes that determine the development of the male or female sex are known in Caenorhabditis elegans, Drosophila, and most mammals. In many other organisms the existence of sex-determining factors has been shown by genetic evidence but the genes are unknown. We have found that in the fish medaka the Y chromosome-specific region spans only about 280 kb. It contains a duplicated copy of the autosomal DMRT1 gene, named DMRT1Y. This is the only functional gene in this chromosome segment and maps precisely to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

16
628
1
9

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 799 publications
(674 citation statements)
references
References 38 publications
16
628
1
9
Order By: Relevance
“…Several sex determination and sex chromosome-linked genes in vertebrates such as Dmy in medaka (Matsuda et al, 2002;Nanda et al, 2002), DM-W in the W chromosome of African clawed frog (Yoshimoto et al, 2008), and Dmrt1 in the Z chromosome of birds (Smith et al, 2009), have been shown to be recently duplicated homologs of Dmrt1. Because of the high evolutionary conservation and the newly recruited role in vertebrates (Herpin and Schartl, 2011;Xia et al, 2007), Dmrt1 also allows us to analyze the evolutionary history of genome duplication through examination of divergence and phylogeny of the duplicated genes.…”
Section: Introductionmentioning
confidence: 99%
“…Several sex determination and sex chromosome-linked genes in vertebrates such as Dmy in medaka (Matsuda et al, 2002;Nanda et al, 2002), DM-W in the W chromosome of African clawed frog (Yoshimoto et al, 2008), and Dmrt1 in the Z chromosome of birds (Smith et al, 2009), have been shown to be recently duplicated homologs of Dmrt1. Because of the high evolutionary conservation and the newly recruited role in vertebrates (Herpin and Schartl, 2011;Xia et al, 2007), Dmrt1 also allows us to analyze the evolutionary history of genome duplication through examination of divergence and phylogeny of the duplicated genes.…”
Section: Introductionmentioning
confidence: 99%
“…In birds, the Z chromosome-linked DMRT1 is the best candidate for a male master testis-determining gene (Nanda et al, 1999). Furthermore, the Y-linked sex determina-tion gene DMY in the teleost Japanese medaka has been shown to be a duplicate of autosomal gene DMRT1 and a relatively recent product in a short period of evolutionary time (Matsuda et al, 2002;Nanda et al, 2002;Zhang, 2004). So DMRT1 is not only conservative but also changeable to fulfill novel functions.…”
Section: Introductionmentioning
confidence: 99%
“…However, contrary to the initial prediction that Sry is conserved among vertebrates, many animals do not possess an Sry homolog. Ten years after the discovery of Sry , DMY / Dmrt1bY was identified as the sex determination gene on the sex chromosome in the teleost fish, medaka 5, 6. Since this discovery, other sex determination genes have also been identified in various vertebrates.…”
Section: Introductionmentioning
confidence: 99%
“…All sex determination genes examined thus far are expressed in the somatic (supporting) cells that directly surround the germ cells in the gonad 3, 4, 5, 6, 7, 8, 9, 10, 11, 12. Therefore, it is reasonable to speculate that the sexual fate of germ cells (in other words, the fate decision of germ cells to develop eggs or sperms) is triggered by the sex of the surrounding somatic cells during a normal sex determination process.…”
Section: Introductionmentioning
confidence: 99%